Role of Anticonvulsants in the Management of Posttraumatic Epilepsy - Kirmani, Batool F.; Robinson, Diana Mungall; Fonkem, Ekokobe; Graf, Kevin; Huang, Jason H. (Frontiers in Neurology, 2016)
Posttraumatic seizures (PTS) have been recognized as a major complication of traumatic brain injury (TBI). The annual incidence of TBI in the United States is 1.7 million. The role of anticonvulsants in the treatment of posttraumatic epilepsy (PTE) remains uncertain. Based on current studies, however, anticonvulsants have been shown to reduce early PTS occurring within the first 7 days, but little to no benefits have been shown in late PTS occurring after 7 days. In this paper, we provide a mini review of the role of anticonvulsants and current advances in the management of PTE.